Large variation in assessment and outcome definitions to describe the burden of long‐term morbidity in childhood cancer survivors: A systematic review. Issue 11 (2nd September 2020) - Streefkerk, Nina; Fioole, Lisanne C.E.; Beijer, Josien G.M.; Feijen, Elizabeth (Lieke) A.M.; Teepen, Jop C.; Winther, Jeanette F.; Ronckers, Cecile M.; Loonen, Jaqueline J.; van Dulmen‐den Broeder, Eline; Skinner, Rod; Hudson, Melissa M.; Tissing, Wim J.E.; et al.
Abstract: We systematically reviewed outcome assessment methods, outcome classification, and severity grading of reported outcomes in studies investigating the burden of physical long‐term morbidity in childhood cancer survivors (CCS). A MEDLINE and EMBASE search identified 56 studies reporting on three or more types of health conditions in 5‐year CCS, for which information was extracted on outcome types and classification, methods of outcome ascertainment, and severity grading. There was substantial variability in classification and types of health conditions reported and in methods of outcome ascertainment. Only 59% of the included studies applied severity grading, mainly the common terminology criteria of adverse events. This large variation in assessment and definition of the burden of physical long‐term morbidity in CCS challenges interpretation, comparison, and pooling data across studies. Global collaboration is needed to standardize assessments and harmonize definitions of long‐term physical morbidity and associated outcomes in childhood cancer survivorship research.